Correction: A new non-fullerene acceptor based on the combination of a heptacyclic benzothiadiazole unit and a thiophene-fused end group achieving over 13% efficiency. Issue 3 (20th December 2019) - Zhang, Yunqiang; Cai, Fangfang; Yuan, Jun; Wei, Qingya; Zhou, Liuyang; Qiu, Beibei; Hu, Yunbin; Li, Yongfang; Peng, Hongjian; Zou, Yingping
Abstract : Correction for 'A new non-fullerene acceptor based on the combination of a heptacyclic benzothiadiazole unit and a thiophene-fused end group achieving over 13% efficiency' by Yunqiang Zhang et al., Phys. Chem. Chem. Phys., 2019, DOI: ; 10.1039/c9cp05015a .